Discriminating lineages of Batrachochytrium dendrobatidis using quantitative PCR. (12th February 2021) - Ghosh, Pria N.; Verster, Ruhan; Sewell, Thomas R.; O'Hanlon, Simon J.; Brookes, Lola M.; Rieux, Adrien; Garner, Trenton W. J.; Weldon, Ché; Fisher, Matthew C.
Abstract: The ability to detect and monitor infectious disease in a phylogenetically informative manner is critical for their management. Phylogenetically informative diagnostic tests enable patterns of pathogen introduction or changes in the distribution of genotypes to be measured, enabling research into the ecology of the pathogen. Batrachochytrium dendrobatidis ( Bd ), a causative agent of chytridiomycosis in amphibian populations, emerged worldwide in the 21st century and is composed of six lineages which are display varying levels of virulence in their hosts. Research into the distribution, ecology and pathogenicity of these lineages has been hampered by an inability to type lineage efficiently. Here, we describe a lineage‐specific TaqMan qPCR assay that differentiates the two lineages of Bd most commonly associated with chytridiomycosis: Bd GPL and Bd CAPE. We demonstrate how this assay can be used for the surveillance of wild populations of amphibians in Southern Africa using skin swabs, tissue samples and cultured isolates. Abstract : see also the Perspective by Claudio Azat